HUBUNGAN PENGALAMAN LAPANGAN INDUSTRI DAN MOTIVASI KERJA DENGAN KESIAPAN KERJA LULUSAN PROGRAM STUDI PENDIDIKAN KESEJAHTERAAN KELUARGA - Rusmiati, Tika; Yulastri, Asmar,; Gusnita, Wiwik (Journal of Home Economics and Tourism, 2016)
The purpose of this study was to (1) analyze the relationship industry field experiencewith the job readiness of graduates, (2) analyze the relationship between workmotivation and job readiness of graduates, (3) analyze the relationship betweenindustry field experience and motivation to work with the job readiness of graduates.This research is a quantitative research using correlation approach. The datacollection technique using a questionnaire prepared by the "Likert Scale". Analysis ofthe data used is descriptive and correlational analysis. The results showed (1) Field Experience Industry has a positive and significant relationship with the ReadinessWork Graduate Studies Program of Family Welfare as indicated by the calculatedvalue coefficient of correlation of 0.562, (2) Work motivation has a positive andsignificant relationship with the Readiness Work Graduate Education ProgramFamily welfare as indicated by the calculated value correlation coefficient of 0.482(3) Field experience and Motivation Industry Working together has a positive andsignificant relationship with the Work Readiness Program Graduate EducationStudies of Family welfare as indicated by the double correlation coefficientscalculated value obtained 0.617.Keywords : Field Experience Industry, Work Motivation, Job Readiness